From Depletion to Regeneration: Addressing Structural and Physical Violence in Post-Conflict Economies. (8th January 2020) - Rai, Shirin M; True, Jacqui; Tanyag, Maria
Abstract: Drawing on depletion through social reproduction and political economy of violence against women (PEVAW) approaches, we show how the context of violence intensifies the depletion of women's lives as they labor to meet their household needs; and how this depletion heightens their vulnerability to violence in conflict-affected contexts and inhibits their roles in peacebuilding. We propose the concept of the "regenerative state, " as a post-conflict moment of openness when state policy underpinned by attention to issues of depletion, social reproduction, and violence against women can help reshape gendered power relations in post-conflict transitions.